770. Otherwise Unavailable Non-Malarial Parasitic Disease Treatment Drugs in the United States: an Update from CDC Parasitic Diseases Drug Service. (31st December 2020) - Chancey, Rebecca J; Yu, Yon; Yu, Patricia; Jolly, Julian; Montgomery, Susan
Abstract: Background: The Centers for Disease Control and Prevention's (CDC) support to clinicians includes providing access to certain drugs exclusively available through CDC for diseases that lack, or have limited market availability of, FDA-approved therapeutics in the U.S. These drugs are provided by CDC under expanded access Investigational New Drug (IND) applications, authorized by the FDA, to treating physicians. The CDC Parasitic Diseases Drug Service provides treatment drugs for patients with parasitic diseases, including travelers, immigrants and refugees from endemic countries. Methods: CDC's records for patients for whom drug was released over a 10-year period were reviewed. Results: From 2010–2019, the annual number of drug releases for patient treatment ranged from 21–113 (median 99). Benznidazole, a treatment for Chagas disease, was the most common drug released for patients between 2012–2018, ranging from 42–63% of total drug releases annually. Sodium stibogluconate (Pentostam® 1 ), for treatment of certain presentations of cutaneous, visceral, and mucocutaneous leishmaniasis, accounted for 6–22% of annual releases over the last 10 years. While requests for treatment for human African trypanosomiasis are rare, in 2019 CDC released eflornithine and nifurtimox for one patient who met criteria for treatment according to the 2019 WHO recommendations. 2 Conclusion: Recent changes to release frequency of triclabendazole, benznidazole, nifurtimox, and sodium stibogluconate are likely due to FDA-approval and commercial availability of previously investigational drugs. Triclabendazole is now FDA approved for treatment of Fasciola infection in persons ≥6 years old and benznidazole is now FDA approved for treatment of Chagas disease in children 2–12 years old. Miltefosine has also been approved by FDA for treatment of certain leishmaniasis infections. CDC has successfully pursued expiry extensions of drugs with manufacturers, FDA, and other partners to ensure continued domestic availability of treatment options when there has been no or limited production of newer lots. CDC's Parasitic Diseases Branch can be reached by telephone: 404-718-4745 or email: parasites@cdc.gov. 1 Pentostam® is made by GlaxoSmithKline 2 WHO interim guidelines for treatment of gambiense HAT. Geneva: 2019. Disclosures: All Authors : No reported disclosures